BACCHUS: A randomised non-comparative phase II study of neoadjuvant chemotherapy (NACT) in patients with locally advanced rectal cancer (LARC) - R. Glynne-Jones; M.R. Hall; A. Lopes; S. Pearce; V. Goh; S. Bosompem; J. Bridgewater; I. Chau; H. Wasan; B. Moran; L. Melcher; N.P. West; et al. (Heliyon, 2018)
Background: Chemoradiation (CRT) or short-course radiotherapy (SCRT) are standard treatments for locally advanced rectal cancer (LARC). We evaluated the efficacy/safety of two neoadjuvant chemotherapy (NACT) regimens as an alternative prior to total mesorectal excision (TME). Methods/design: This multi-centre, phase II trial in patients with magnetic resonance imaging (MRI) defined high-risk LARC (>cT3b, cN2+ or extramural venous invasion) randomised patients (1:1) to FOLFOX + Bevacizumab (Arm 1) or FOLFOXIRI + bevacizumab (Arm 2) every 14 days for 6 cycles prior to surgery. Patients were withdrawn if positron emission tomography (PET) standardised uptake value (SUV) after 3 cycles failed to decrease by >30% or increased compared to baseline. Primary endpoint was pathological complete response rate (pCR). Secondary endpoints included adverse events (AE) and toxicity. Neoadjuvant rectal (NAR) scores based on “T” and “N” downstaging were calculated. Findings: Twenty patients aged 18–75 years were randomised. The trial stopped early because of poor accrual. Seventeen patients completed all 6 cycles of NACT. One stopped due to myocardial infarction, 1 poor response on PET (both received CRT) and 1 committed suicide. 11 patients had G3 AE, 1 G4 AE (neutropenia), and 1 G5 (suicide). pCR (the primary endpoint) was 0/10 for Arm 1 and 2/10 for Arm 2 i.e. 2/20 (10%) overall. Median NAR score was 14·9 with 5 (28%), 7 (39%), and 6 (33%) having low, intermediate, or high scores. Surgical morbidity was acceptable (1/18 wound infection, no anastomotic leak/pelvic sepsis/fistulae). The 24-month progression-free survival rate was 75% (95% CI: 60%–85%). Interpretation: The primary endpoint (pCR rate) was not met. However, FOLFOXIRI and bevacizumab achieved promising pCR rates, low NAR scores and was well-tolerated. This regimen is suitable for testing as the novel arm against current standards of SCRT and/or CRT in a future trial.